2018
DOI: 10.1002/ejic.201801219
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Recent Advances in Phosphorene Functionalization and Its Applications in Devices

Abstract: Phosphorene, the 2D material derived from black phosphorus, has recently attracted a lot of interest for its properties, suitable for applications in materials science. The physical features and the prominent chemical reactivity on its surface render this nanolayered substrate particularly promising for electrical and optoelectronic applications. In addition, being a new potential ligand for metals, it opens the way for a new role of the inorganic chemistry in the 2D world, with special reference to the field … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 251 publications
(440 reference statements)
0
47
0
2
Order By: Relevance
“…In recent years, 2D pnictogen, group‐VA atomic sheet (phosphorene, arsenene, antimonene, and bismuthene) have achieved remarkable progress and is considered to be a competitive candidate for next‐generation logic devices due to their fascinating physicochemical properties, such as tunable bandgap and controllable stability except arsenene because of its high toxicity. [ 1–3 ] Until now, many comprehensive and impressive reviews have been published on topics related to phosphorene, [ 4–9 ] and antimonene. [ 10 ] For example, Zhang and co‐workers [ 5 ] systematically summarized the recent developments in black phosphorus (BP), including the synthetic approaches for fabricating single or few‐layer BP, the recent advances in its optical, electronic, and mechanical properties, and the related devices.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, 2D pnictogen, group‐VA atomic sheet (phosphorene, arsenene, antimonene, and bismuthene) have achieved remarkable progress and is considered to be a competitive candidate for next‐generation logic devices due to their fascinating physicochemical properties, such as tunable bandgap and controllable stability except arsenene because of its high toxicity. [ 1–3 ] Until now, many comprehensive and impressive reviews have been published on topics related to phosphorene, [ 4–9 ] and antimonene. [ 10 ] For example, Zhang and co‐workers [ 5 ] systematically summarized the recent developments in black phosphorus (BP), including the synthetic approaches for fabricating single or few‐layer BP, the recent advances in its optical, electronic, and mechanical properties, and the related devices.…”
Section: Introductionmentioning
confidence: 99%
“…The exploration of new 2D materials starting from other elements of the periodic table led to the discovery of other semiconducting 2D materials, such as 2D black phosphorus (BP) whose single layer is named phosphorene. 2 The most appealing property of 2D BP is surely the direct thickness-dependent band gap, which changes from 0.33 eV for the bulk to 2.26 eV for the single layer. 3 Owing to the high optical absorbance efficiency, combined with a high anisotropy, and the direct band gap, this material is a promising candidate for optoelectronic and photonic applications in the near-mid infrared range.…”
Section: Introductionmentioning
confidence: 99%
“…The main issue with phosphorene is the fast degradation under ambient conditions as a result of the generation of reactive oxygen species. Research however has shown that incorporating phosphorene into polymers preserves the structure and properties of phosphorene [ 16 , 17 ]…”
Section: Introductionmentioning
confidence: 99%